Lama, luto e luta: a vivência dos atingidos pelo desastre da Samarco e a organização popular no Movimento dos Atingidos por Barragens (MAB) como estratégia de enfrentamento - Silva, Camilla Veras Pessoa da (2017)
The present work is the result of a research carried out in the context of the participant observation in the context of the technological disaster caused by the rupture of the Fundão Dam, on 05/11/2015, of the mining company Samarco SA (Vale and BHP Billiton) in the region of Mariana-MG. A theoretical and bibliographical survey was also carried out regarding the conditions in which the disaster occurred and its environmental and psychosocial consequences, pointing to the overproduction, inherent to the model of mineral exploration in force in Brazil, and the negligence with the security and the monitoring of the dams of tailings and disasters of such magnitude (Poema, 2015). The disaster destroyed entire communities, affected 40 municipalities between the states of Minas Gerais, Espírito Santo and Bahia, and compromised the region's ecosystem and the country's fifth largest river basin, the Rio Doce Basin. In addition to affecting the lives of thousands of people, mostly rural workers, fishermen and traditional communities. The material and symbolic losses are incauculável, with prominence the destruction of the communities of Bento Rodrigues and Paracatu de Baixo. The disaster also killed 19 people. This study sought to understand the subjects' experience through the analysis of the meanings and meanings present in the narratives constructed by those affected by the disaster. In addition to seeking to reflect how the popular organization through a popular movement, in this case the Movement of Dam Affected (MAB), could strengthen processes of community resistance. It was concluded that the biopsychosocial impacts produced by the disaster situation produced a condition of psychosocial trauma (MARTÍN-BARÓ, 2000) and of ethical-political suffering (SAWAIA, 2014). In addition, it can be observed that the political participation of those affected, organized in a popular movement, generated subjective transformation, elaboration of a new sense of life and promoted health in the ethical-political perspective. The collective organization in the context of disaster has therefore become an alternative to confront the populations of the region, who up to now experience the consequences of the tragedy in their lives